SOFC-APU systems for aircraft: A review. (16th August 2018) - Fernandes, M.D.; de P. Andrade, S.T.; Bistritzki, V.N.; Fonseca, R.M.; Zacarias, L.G.; Gonçalves, H.N.C.; de Castro, A.F.; Domingues, R.Z.; Matencio, T.
Abstract: This review brings together publications in the form of articles, reports, theses and patents related to the use of solid oxide fuel cells in aircraft with a focus on replacing the current auxiliary units with a hybrid system. The potential advantages and main challenges of the new technology are reported, indicating some possible trends in this technology. However, even after many studies, some initial challenges remain. For example, the hybrid system did not achieve the necessary weight-efficiency-ratio, and there seems to be no consensus on the choice of the best fuel. We conclude that the most viable short-term applications appear to be unmanned units, particularly because of security issues and low technology maturity. Smaller power applications, in which the new system is responsible for peripheral services such as a power supply for air conditioning, toilets, and heating up food, are candidates to enter the market in the short or medium term. In the long term, applications for fully electric aircraft and clean fuels will certainly be the focus of larger aircraft manufacturers. Highlights: An overview of aircraft SOFC-APU systems is provided. Conventional aircraft APUs are primarily responsible for air and noise pollution at airports. Aircraft fuel cell-APUs are the most promising devices to replace conventional APUs. Aircraft SOFC-APUs operate with aviation fuel and greatly reduce the air and noise pollution of aircraft. SOFC technology needs to mature to be used in aircraft.